EFFECTS OF PROBIOTICS ON STRENGTH AND POWER PERFORMANCE IN A TRAINED POPULATION: A SYSTEMATIC REVIEW AND META-ANALYSIS (Kinesiology, 2023)
The main purpose of this systematic review and meta-analysis was to evaluate the effects of probiotics intake on strength and power performance in a trained population. This study was designed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement guidelines. The review was registered in PROSPERO with the following registration number: CRD42021248173. PubMed/MEDLINE, Web of Science, and Scopus databases were searched from their inception to the 18th March 2022 to find original research studies evaluating the effects of probiotic supplementation on strength and power performance tests in a trained population. The following inclusion criteria were applied to select studies: probiotics supplementation; trained population; strength and power performance measurements; human experimental trial; controlled with a placebo group; peer-reviewed and original articles written in English language. Random effects model and standardized mean differences (SMD) were used following Hedges’ G for the meta-analysis. Seven studies were finally included after the inclusion/exclusion criteria were applied (n=142 participants). Results of the meta-analysis identified a significant benefit of probiotics compared to placebo treatments (p=.04), with a small pooled effect size (SMD=0.36 [0.02-0.70]; I2=43%), and no funnel plot asymmetry was present. In summary, this systematic review and meta-analysis demonstrated that probiotic supplementation could effectively enhance strength and power performance in a trained population.Key words: recovery, physiology, nutrition, exercise, athlete